COMPARISON OF DJIKSTRA ALGORITHM AND SPANNING CYCLE DETERMINING SHORTEST PATH - Erwin Panggabean; Desi Vinsensia; Wanra Tarigan; Logaraj Logaraj; Tiara W Pratiwi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: Problems that often occur in people with the growth and development of urban areas that change very quickly cause the movement of people or road users to become chaotic as in the Municipality of Medan. People in carrying out their daily activities are directly influenced by irregular patterns of human movement, in this case what is meant is an increase in congestion, delays, and others. Therefore we need a system that can make it easier for humans to use road facilities, namely a geographic information system to determine the shortest path using the djikstra method and spanning cycle using graphs as a branch of mathematics and computer science. This research activity plan is carried out in the Medan city area using spatial image data from the Medan city map, spatial data based on google maps, and attribute data. a branch of mathematics and computer science. This research activity plan is carried out in the Medan city area using spatial image data from the Medan city map and spatial data based on google maps. The final result of the research that is expected is that the results of the comparison of the two algorithms are obtained according to the spatial data used, and the results of the research will be published in an accredited national journal article with sinta 4 or better. Keywords: comparative of djikstra and spanning cycle method; shortest path; spatial  data  Abstrak: Permasalahan yang sering terjadi pada masyarakat dengan pertumbuhan dan perkembangan kawasan perkotaan yang berubah sangat cepat menyebabkan pergerakan masyarakat atau pengguna jalan menjadi semrawut seperti di Kotamadya Medan. Masyarakat dalam melakukan aktivitasnya sehari-hari secara langsung dipengaruhi oleh pola pergerakan manusia yang tidak teratur, dalam hal ini yang dimaksud adalah peningkatan kemacetan, keterlambatan, dan lain-lain. Oleh karena itu diperlukan suatu sistem yang dapat mempermudah manusia dalam menggunakan fasilitas jalan yaitu sistem informasi geografis untuk menentukan jalur terpendek dengan menggunakan metode djikstra dan spanning cycle menggunakan graf sebagai cabang dari matematika dan ilmu komputer. Rencana kegiatan penelitian ini dilakukan di wilayah kota Medan dengan menggunakan data citra spasial dari peta kota Medan, data spasial berbasis google maps, dan data atttributnya. Hasil akhir dari penelitian yang diharapkan adalah diperoleh hasil perbandingan kedua algoritma sesuai dengan data spasial yang digunakan, dan luaran hasil penelitian akan dipublish pada artikel jurnal nasional terakreditasi sinta 4 atau yang lebih baik. Kata kunci: data spasial ; jalur terpendek;perbandingan metode djikstra dan spanning cycle